2016
DOI: 10.1097/md.0000000000005654
|View full text |Cite
|
Sign up to set email alerts
|

The anhepatic phase extended by temporary portocaval shunt does not affect anesthetic sensitivity and postoperative cognitive function

Abstract: Temporary portocaval shunt (TPCS) prolongs the duration of the anhepatic phase, during which anesthetic sensitivity is highest among the 3 phases of living donor liver transplantation (LDLT). Cognitive dysfunction has been associated with increased anesthetic sensitivity and poor hepatic function. Therefore, we assessed anesthetic sensitivity to desflurane and perioperative cognitive function in patients undergoing LDLT, in whom the duration of the anhepatic phase was extended by TPCS to test the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
4
0
4
Order By: Relevance
“…Only two studies, by Rayar et al 3 and Weniger et al, 18 found an increase surgical time in the group undergoing TPCS. In cases where there was an increase in the anhepatic phase in the TPCS group, as in the prospective study conducted by Son et al, 17 there was no impact on anesthetic sensitivity or postoperative cognitive function.…”
Section: Surgery Timementioning
confidence: 61%
See 1 more Smart Citation
“…Only two studies, by Rayar et al 3 and Weniger et al, 18 found an increase surgical time in the group undergoing TPCS. In cases where there was an increase in the anhepatic phase in the TPCS group, as in the prospective study conducted by Son et al, 17 there was no impact on anesthetic sensitivity or postoperative cognitive function.…”
Section: Surgery Timementioning
confidence: 61%
“…The same was seen in a retrospective study of Nacif et al, 16 while other authors reported that there was no difference. 2,7,15,17 According to Belghiti et al, 8 the average time to perform the shunt is 9 minutes, and for Faitot et al 9 the time varies between 5 and 15 minutes. Only two studies, by Rayar et al 3 and Weniger et al, 18 found an increase surgical time in the group undergoing TPCS.…”
Section: Surgery Timementioning
confidence: 99%
“…Of these systematic reviews, we selected 28 cases to further assess. We analyzed all articles regarding liver transplantation [ 1 , 4 6 , 13 24 ], 3 articles describing HPCS [ 4 6 ], and 10 articles describing TPCS [ 1 , 13 18 , 20 , 23 , 24 ]. In Figure 2 we show the flow diagram of the systematic literature search, according to PRISMA statement.…”
Section: Resultsmentioning
confidence: 99%
“…Lo mismo fue visto en estudio retrospectivo de Nacif et al, 16 mientras otros autores relataron que no hubo diferencia. 2,7,15,17 Según Belghiti et al, 8 el tiempo promedio para la realización del shunt es de 9 minutos, y para Faitot et al 9 el tiempo varía entre 5 y 15 minutos.…”
Section: Tiempo De Cirugíaunclassified